The liberation of women : and, The new woman : two documents in the history of Egyptian feminism - Qāsim Amīn, 1863-1908,
"In the first of these important books in 1899, he started from the premise that liberation of women was an essential prerequisite for the liberation of Egyptian society from foreign domination, and used arguments based on Islam to call for an improvement in the status of women. In doing so, he promoted the debate on women in Egypt from a side issue to a major national concern, but he also subjected himself to severe criticism from the khedival palace, as well as from religious leaders, journalists, and writers. In response he wrote The New Woman, published in 1900, in which he defended his position and took some of his ideas further. In The New Woman, Amin relies less on arguments based on the Quran and Sayings of the Prophet, and more openly espouses a Western model of development. Although published a century ago, these two books continue to be a source of controversy and debate in the Arab world and remain key works for understanding the Arab feminist movement. The Liberation of Women and The New Woman appear here in English translation for the first time in one volume." -- BOOK JACKET.